Analysis Of The Influence Of The Work Environment, Career Development And Work Responsibility On Job Satisfaction In The Personnel Agency And Resource Development Humans In Binjai City - Shintya; Emi Wakhyuni; Darmilisani (Yayasan Multidimensi Kreatif, 2025)
The research analysis aims to find out whether the work environment, career development and job responsibility affect job satisfaction. The data analysis technique used is an associative research method with the help of the SPSS version 25 program. This study uses multiple linear regression analysis. The sample in this study was 39 respondents. Primary data collection uses questionnaires. The results of the study show that the tcount value is 3.440 > ttable is 2.03 with a significant value of 0.002 < 0.05, then the H3 hypothesis is accepted and H0 is rejected, meaning that responsibility has a positive and partially significant effect on the job satisfaction of employees of the Personnel and Human Resources Development Agency in Binjai City. The calculation value of 0.854 < table of 2.03 with a significant value of 0.399 > 0.05, then the H2 hypothesis was rejected and H0 was accepted, meaning that career development did not have a significant partial effect on job satisfaction. The calculation value is 2.581 > the table is 2.03 with a significant value of 0.014 < 0.05, then the H3 hypothesis is accepted and H0 is rejected, meaning that responsibility has a positive and partially significant effect on job satisfaction. The value of F is calculated as 53.520 which is greater than 2.87 and the significant value of 0.000 is less than 0.05 so it can be concluded that hypothesis 4 is accepted and hypothesis 0 is rejected, namely work environment, career development and responsibility have a significant effect simultaneously on job satisfaction.